2018
DOI: 10.1051/matecconf/201825106027
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Risk Assessments in Project Management in Construction Industry

Abstract: Modern economic conditions require construction companies to promptly prevent, identify and manage risks in various areas of their construction activities. As this research shows, many of the best practices of corporate risk management are adopted and applied in large Russian construction companies and in various industries. At the same time, the results of the research demonstrate the possibilities for further development. Key areas of development include: the process of integrating risk management into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…additional 15 and 20 minute breaks for temperature rehabilitation due to the limit values of weather hardness and the creation of appropriate rehabilitation procedure. The model also calculates the probability [17][18][19] of absenteeism due to diseases associated with severe weather. Figure 3 shows the dependence of the possible values of injuries of construction workers due to the severity of the weather.…”
Section: Resultsmentioning
confidence: 99%
“…additional 15 and 20 minute breaks for temperature rehabilitation due to the limit values of weather hardness and the creation of appropriate rehabilitation procedure. The model also calculates the probability [17][18][19] of absenteeism due to diseases associated with severe weather. Figure 3 shows the dependence of the possible values of injuries of construction workers due to the severity of the weather.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, some financial institutions and investors do not invest in construction projects, explaining their actions are due to increased level of risk in construction industry. [6][7][8][9] According to the ISO 31000 international risk management standard in construction projects, risk can be defined as the probability of an event that impairs the viability of a project [10] Not all risks should be associated with negative results, because, although in most cases this happens, risks can also mean potential opportunities. From the time the project objectives are set, construction time, cost, and quality are the most important risk factors to consider.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that the construction industry is subject to multiple sources of internal and external risk, highlighting the investment climate, inflation, the dynamics of effective demand, and social responsibility for the safety of projects. [1][2][3][4][5][6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…In these methods the estimated effects of the event and the probability or frequency of occurrence of certain effects are attributed to conventional qualities characterizing their value. The assigned qualities can be descriptive or measured by the quality of something rather than its quantity [21]. The choice of the methods depends on the type of the assessed work process, the type of hazards, and availability of data.…”
Section: Introductionmentioning
confidence: 99%